A study on the relationship between journal writing and Malaysian ESL learners' writing performance among UiTM students / Muhammad Syafiq Mazlan - Mazlan, Muhammad Syafiq (2015)
English writing is considered as an important language skill to be learnt and thus, the educational institutions have acknowledged the importance of acquiring English. The study aims to investigate the effects of journal writing on Malaysian ESL Learners' writing performance. The objectives of this study are to investigate the effects of journal writing towards Malaysian ESL Learners' writing performance in terms of Overall, Content and Language Use scores between two independent groups namely Experimental and Control Group. This study employed experimental research design in gathering the data. 61 Diploma students from two different classes at Universiti Teknologi Mara Alor Gajah, were chosen as respondents for this study. The respondents were assigned into two groups, namely Journal Writing Instruction Class (Experimental Group) and Conventional Writing Instruction Class (Control Group). Sets of questionnaire were given to both groups to gain their demographic background. Pre and post writing test were administered to identify the differences between Overall, Content and Language Use scores of their ESL writing performance. These scores were compared between the two groups. Interview sessions were conducted on week-14 in gaining the ESL Learners' perspective towards journal writing integration. After going through 14-week of learning process, quantitative and qualitative findings revealed that Experimental Group performed better in Overall, Content and Language Use scores. This study employed an experimental which is appropriate for the nature of this study. The data collected were analyzed using SPSS to identify the correlation of journal writing and ESL writing performance. The data were analyzed statistically using several tools of test in providing strong evidence. Analysis of Variance, Sample T-Test, Frequencies and Mean Scores were used in producing the findings. These findings indicated that students from Experimental Group showed good improvement in their ESL writing performance where majority of the students had an improved writing score. The findings from the interview sessions revealed that the respondents felt journal writing had helped them to improve their ESL writing performance. Besides, they believed the advantages of journal writing outweighed the difficulties of journal writing implementation. This study hopes to provide ESL educators with useful insights in integrating journal writing in their ESL writing classes.